Violence, Criminal Subjection and Political Merchandise in Brazil: An Overview from Rio - Misse, Michel (International Journal of Criminology and Sociology, 2018)
The author examines the main dimensions of urban violence in the case of Rio de Janeiro, which includes criminal prosecution of violent collective actors and the participation of policemen in the offer of "political merchandise" to the same actors that the police repress.